Combined use of Solitaire FR and Penumbra devices for endovascular treatment of cerebral venous sinus thrombosis in a child. (19th February 2014) - Shaikh, Hamza; Pukenas, Bryan Anthony; McIntosh, Adeka; Licht, Daniel; Hurst, Robert W
Abstract : A pre-teenager with newly diagnosed ulcerative colitis presented to an emergency department with acute headache, altered mental status and bilateral lower extremity weakness. Head CT demonstrated acute thrombus in the vein of Galen and straight sinus, and the patient was started on a heparin infusion. The patient clinically deteriorated and became unresponsive. In view of the rapid deterioration despite anticoagulation therapy, the patient was taken for endovascular treatment. A novel endovascular approach was performed with combined use of Solitaire FR and Penumbra devices to enhance access to the straight sinus and to limit intraprocedural blood loss. The post-treatment head CT demonstrated a decrease in hyperattenuation within the vein of Galen and straight sinus. The neurologic status improved within 24 h. The patient was discharged home with a normal neurologic examination.